Misuse of Artificial Intelligence in Cybercrime: Criminal Liability and Electoral Integrity - Hadi Jumhadi; Dini Dewi Heniarti (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study examines the misuse of artificial intelligence (AI) from the perspective of cybercrime and its implications for electoral integrity. The rapid development of AI has transformed cybercrime from conventional, human-centered acts into autonomous, large-scale, and structurally complex operations capable of manipulating public perception and democratic processes. This research aims to analyze the characteristics of AI-enabled cybercrime in elections, assess the applicability of the classical concept of mens rea in crimes involving autonomous systems, and formulate adaptive models of criminal liability in response to these challenges. The study employs a qualitative legal research method with a normative and conceptual approach. Data are collected through library research using primary legal materials in the form of statutory regulations and secondary legal materials consisting of scholarly articles, legal doctrines, and relevant academic publications. The analysis is conducted through descriptive-analytical techniques, legal interpretation, and conceptual analysis. The findings demonstrate that AI-driven cybercrime creates ontological and epistemological challenges for criminal law, particularly in attributing intent and responsibility. As AI cannot be recognized as a legal subject, criminal liability must be reconstructed and directed toward human and institutional actors through layered and contextual liability models. The novelty of this research lies in its integration of mens rea theory with the structural characteristics of AI-enabled cybercrime, offering a proactive and anticipatory criminal law framework to safeguard electoral integrity in the digital era.